Effectiveness of the teaching practice program for preparing students teachers at Education Faculty in Arhab - Sana'a University from Students' perspectives in the Academic year 2015/2016 - Ruqiah Naji Al-Duais (University of Science and Technology, Yemen, 2018)
The study aimed to explore the degree of effectiveness of teaching practice course in the bachelor degree of Teacher Education Preparation at the Faculty of Education, in Sana'a University - Arhab branch, from Students' perspectives in the Academic year 2016/2017. To achieve this aim, a questionnaire, consisting of 61 items was developed. The questionnaire covered four dimensions: educational supervisor, cooperative teacher, cooperative school, and development of educational competencies. A sample of (66) students were selected randomly from the fourth level. The study results showed that the highest degree of effectiveness was in the dimension of "development of educational competencies" which scored a mean of (3.02), which also indicated a medium degree of effectiveness. The next score was to the dimension of "educational supervisor" which was (2.63). The other two dimensions, "the cooperating teacher" and "the cooperating school", scored the means of (1.40), (1.86) respectively. These two values indicate low degree of effectiveness. Finally, the study presented recommendations that would contribute to the development of the teaching practice program in the colleges of education of Sana'a University to achieve the desired objectives. Keywords: Teaching practice, Faculty of Education, Arhab, Sana'a University, Student teacher preparation